2010
DOI: 10.1111/j.1542-474x.2010.00352.x
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Left Ventricular Morphology Outperform Left Ventricular Mass for Prediction of QRS Duration

Abstract: The model for prediction of QRS duration opens the ability to predict case-specific normal QRS duration. This knowledge can have clinical importance, when determining the normality on case-specific basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
0
12
0
1
Order By: Relevance
“…The correlation between papillary muscle angle and QRSd in healthy patients 1 was not present in cardiomyopathy patients. Figure 3A shows electrical activation in normal conduction patients starting in the endocardium and papillary muscles.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…The correlation between papillary muscle angle and QRSd in healthy patients 1 was not present in cardiomyopathy patients. Figure 3A shows electrical activation in normal conduction patients starting in the endocardium and papillary muscles.…”
Section: Discussionmentioning
confidence: 77%
“…Previous studies in healthy subjects with normal conduction demonstrated that LV mass, 2,1 LV length 1 , LV diameter, 2 and LV wall thickness 2 all correlated with QRSd. Our findings are also consistent with results of previous studies in patients with known cardiovascular disease, where QRS duration was associated with LV mass and LVEDV.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Ez csak egy kisebb, egyetlen vizsgáló-helyen igazolt eredmény, amelyet nyilván nagyobb, multicentrikus vizsgálatokban is igazolni szükséges. A legfrissebb vizsgálatok arra is utalnak, hogy a digitalizált EKG-feldolgozás numerikus adatai alkalmasak lehetnek a bal kamrai űrtér és morfológia egyéni különb-ségeinek normalizálására, azaz az úgynevezett "esetspecifi kus" QRS-időtartam meghatározására [27], amely tovább pontosíthatja a CRT indikációját.…”
Section: áBraunclassified